WORK MOTIVATION AND EMPLOYEE ENGAGEMENT AS PREDICTORS OF TURNOVER INTENTION - Safitri, Ria; Hartati, Wiwi; Sylvani, Sylvani (Politeknik Negeri Ambon, 2025)
Introduction: This study examines the relationship between the intention to leave among PT X workers and their degrees of job motivation and engagement. The company has recently experienced a high turnover rate, which has challenged operational consistency and increased hiring costs. Turnover intention denotes an employee's inclination to quit their position, shaped by several organizational and psychological factors. Intrinsic and extrinsic job motivation, along with employee engagement —defined as the emotional and intellectual involvement of employees in their work —are considered to impact this purpose significantly. Methods: A quantitative explanatory research methodology was employed, utilizing a saturated sample of 234 employees. Questionnaires gathered data. Questionnaire data were gathered, and multiple linear regression analysis was performed using SPSS.. Assessments of validity and reliability were essential to the instrument procedure, followed by t-tests and F-tests performed at a 5% significance level to evaluate the hypothesis. Results: The data indicate that there is no statistically significant relationship between employee engagement and the intention to leave. Conversely, employment motivation demonstrates a substantial negative correlation, suggesting that as an employee's drive escalates, their likelihood of leaving the firm decreases. Turnover intention is significantly affected by job motivation and employee engagement. The results indicate that while employee involvement is crucial, reducing turnover intentions may be more effectively achieved by enhancing job motivation. To retain talent and minimize employee turnover, organizations are advised to adopt incentive methods, including career progression, recognition, and equitable compensation frameworks. Keywords: Employee Engagement, Work Motivation, Turnover Intention